(untitled) (UUM Journal of Legal Studies, 2023)
The International humanitarian law, through a set of international conventions, protects prisoners of war from any violation or infringement of human rights during their captivity. The status of prisoners of war is only applicable in international armed conflicts. After The Hague Convention had failed to identify the categories of fighters who would benefit from their privileges as prisoners of war in World War II, the Third and Fourth Geneva Conventions and their protocols were established to justify the inclusion of broader categories of combatants. Descriptive and analytical approaches are used in the study reported in this article to identify the category of people regarded as prisoners of war. by examining international treaties and agreements in relation to the definition of a prisoner of war before characterising the individuals who fulfil the criteria of “prisoner of war” under these treaties. Moreover, it explains the legal mechanisms necessary to ensure that the parties involved in international conflicts comply with the international conventions on prisoners of war. This article concludes that the prisoners of war are often members of the military forces of one of the belligerents who fall into the hands of the opposing party and other types of people who possess the right to the status of prisoners of war or can be treated as prisoners of war following the Third Geneva Convention of 1949. In contrast, traitors, deserters and mercenaries are not considered the prisoners of war. If they commit a war crime, they can be prosecuted by the internal law of the Detaining Power. On the other hand, the overlapping definitions of the prisoners of war can create confusion in combatant interactions during the armed conflict, hence increases violations. Consequently, states must take practical steps to prevent any expected violations against the prisoners of war, for instance enacting national laws to ensure international treaties compliance and raise the awareness of international law among leaders and officials during armed conflicts to limit the violence against combatants.